Do agenda 2030 and Sustainable Development Goals act at local and operational levels? Evidence from a case study in a large energy company in Italy. Issue 4 (3rd August 2020) - Battaglia, Massimo; Annesi, Nora; Calabrese, Mario; Frey, Marco
Abstract: This paper investigates the relationship between the business orientation to sustainability read under the lens of viable systems, and the operational and local dimensions of the Sustainable Development Goals (SDGs). The study deals with the experience of an Italian company operating as a monopolist in the energy industry, and it focuses on three innovative power transmission lines built in the 2000s. All the construction processes are analysed in order to explore both the operational effects and local impacts from a sustainability perspective. Embedding sustainability in a company actively contributes to the SDGs and creates a new interpretive model.